World Politics: Trend and Transformation, 17th Edition - Shannon Blanton (Cengage Learning, 2020)
Drawing from the latest research and real-world events, Blanton/Kegley's WORLD POLITICS: TREND AND TRANSFORMATION, 17th Edition, helps you understand what is happening on the international political stage -- and why. Thought-provoking discussions encourage you to critically assess the problems, payoffs, pitfalls and paradoxes of people's choices about the global future and the likely long-term impact of those choices. Coverage includes recent challenges to global peace and prosperity; changes in the political landscape sparked by Brexit, the rise of China and enduring rivalries; terrorism and advances in military capabilities; human rights and inequality; threats to global health and the environment; and more. The Carnegie Council for Ethics in International Affairs provides further insight into emerging issues. Coverage reflects the most recent academic literature and many diverse perspectives. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.